Menilik Potensi dan Konsekuensi dalam Mekanisme Self-Declare Halal - Pratama, Herdifa (Indonesia, 2024)
The idea of halal certification (self-declare halal) is increasingly being voiced among SMEs. This flow of ideas began with the publication of Law Number 33 of 2014 concerning Halal Product Guarantees which then legitimized the evolution from an idea to a mission to make it easier for every MSE. That’s wat it’s called “Self-Declare Halal”. This Research focuses on the study of self-declare halal which has potentials and consequences in it. This study aims to examine the results of identification regarding the potential and consequences contained in the halal self-declaration mechanism. This literature study-based research use the secondary data which is then analyzed using a descriptive-analytic approach. This study found research findings that halal self-declaration has the potential to be a breakthrough and accelerate halal certification for MSMEs. This will have an impact on increasing the guarantee of halal products in Indonesia, especially products originating from MSMEs. Apart from that, self-declaring halal has consequences in the form of moral deviations that could potentially be carried out by MSME actors (moral hazard). These two potential elements must be the point of view in implementing and achieving the goals of halal self-declaration.